Functionalization of Two-Dimensional Transition Metal Dichalcogenides - CHEN, XIN (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
Two-dimensional transition metal dichalcogenides (2D TMDs) have aroused enormous interest in recent years due to their intriguing properties and a wide array of potential applications. Further tailoring their colloidal and surface properties and fully harnessing their capabilities can be achieved through surface functionalization. In this thesis, two facile avenues to functionalize 2D TMDs with either organic thiols or inorganic complexes are demonstrated. A general route to functionalize exfoliated 2H-MoS2 with organic thiols (e.g., L-cysteine and 1-octanethiol) was initially illustrated in Chapter 2. It was found that instead of adsorption of thiol monomers covalently or datively at sulfur vacancies, functionalization of 2D MoS2 with organic thiols tends to produce the corresponding disulfide species physisorbed on the surface of nanosheets. The kinetic behaviors of 2H-MoS2/1-octanethiol reaction under the inert atmosphere were illustrated in Chapter 3 in order to further elucidate the MoS2 mediated thiol oxidation. The rate of 1-octanethiol oxidation (to dioctyl disulfide) was found to be directly related to the concentration of MoS2 and 1-octanethiol, the thickness of MoS2 nanosheets and the proton transfer process (KIE = 2). In the second approach, a stepwise functionalization strategy was developed (Chapter 4) to covalently bind [RuII(bpy)3]2+-based photosensitizer onto chemically exfoliated MoS2 nanosheets (ce-1T-MoS2). The photoelectrochemical (PEC) measurement of the [RuII(bpy)3]-MoS2 electrode in ascorbic acid displayed a significant improvement of photocurrent generation compared to the non-functionalized MoS2, signifying the potential of the [RuII(bpy)3]-MoS2 covalent assembly in photo-hydrogen production. Efforts to further tune the PEC performance of such dye-sensitized MoS2 system through the covalent incorporation of other photosensitizers were demonstrated in Chapter 5. The PEC performance of the whole dye-sensitized MoS2 device was found to rely on both the surface coverage of photosensitizers and the catalytic activity of functionalized MoS2.
APPROVED
Keywords: Transition Metal Dichalcogenides; Photocatalysis; 2D materials; Hydrogen Evolution Reaction